2018
DOI: 10.3389/fams.2018.00035
|View full text |Cite
|
Sign up to set email alerts
|

Drift and Its Mediation in Terrestrial Orbits

Abstract: The slow deformation of terrestrial orbits in the medium range, subject to lunisolar resonances, is well approximated by a family of Hamiltonian flow with 2.5 degree-of-freedom. The action variables of the system may experience chaotic variations and large drift that we may quantify. Using variational chaos indicators, we compute high-resolution portraits of the action space. Such refined meshes allow to reveal the existence of tori and structures filling chaotic regions. Our elaborate computations allow us to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, in disposal design applications, we are not interested in the chaotic evolution with respect to any of the action variables, but rather in the chaotic behaviour manifesting as eccentricity growth. The fact that the use of chaotic indicators in disposal design can be missleading was also mentioned in a recent work [18]. Therefore, we focus our studies on the eccentricity variations and more specifically, two types of indicators are used.…”
Section: Dynamical Mappingmentioning
confidence: 96%
“…However, in disposal design applications, we are not interested in the chaotic evolution with respect to any of the action variables, but rather in the chaotic behaviour manifesting as eccentricity growth. The fact that the use of chaotic indicators in disposal design can be missleading was also mentioned in a recent work [18]. Therefore, we focus our studies on the eccentricity variations and more specifically, two types of indicators are used.…”
Section: Dynamical Mappingmentioning
confidence: 96%
“…We adopt a simplified sub-model of the quadrupolar doubly-averaged formulation to model the external third-bodies perturbations. The quadrupolar approximation is commonly employed to study medium-Earth orbit dynamics and has already demonstrated its relevance (see e.g., [17,11]).…”
Section: The Doubly-averaged Lunisolar Hamiltonianmentioning
confidence: 99%
“…We adopt a simplified sub-model of the quadrupolar doubly-averaged formulation to model the external third-bodies perturbations. The quadrupolar approximation is commonly employed to study medium-Earth orbit dynamics and has already demonstrated its relevance (see e.g., [17,11]). Starting from the Hamiltonians…”
Section: The Doubly-averaged Lunisolar Hamiltonianmentioning
confidence: 99%